1985
DOI: 10.1093/ptj/65.4.482
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Work-Related Low Back Pain in Physical Therapists

Abstract: The purpose of this study was to determine the incidence of work-related low back pain (LBP) in physical therapists and to identify common characteristics of therapists who reported work-related LBP. Questionnaires were mailed to a random sample of 500 registered physical therapists. Of the 344 (69%) questionnaires returned, 29 percent reported work-related LBP. The initial onset most frequently occurred between the ages of 21 and 30 years and within the first four years of experience as a physical therapist. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
96
6
6

Year Published

1988
1988
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(133 citation statements)
references
References 8 publications
18
96
6
6
Order By: Relevance
“…West and Gardner [7] reported that 16% of physiotherapists first experienced their injury as students, whereas 56% reported their worst injury to have occurred within the first 5 years of working as a physiotherapist. The most common region of injury is the low back [3,4,6,7]. In our study, only 17.7% of physiotherapy students had never experienced LBP.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…West and Gardner [7] reported that 16% of physiotherapists first experienced their injury as students, whereas 56% reported their worst injury to have occurred within the first 5 years of working as a physiotherapist. The most common region of injury is the low back [3,4,6,7]. In our study, only 17.7% of physiotherapy students had never experienced LBP.…”
Section: Discussionmentioning
confidence: 50%
“…To the best of our knowledge, this was the first study that clearly demonstrated the association between undergraduate physiotherapy study and LBP. There are many reports in the literature concerning the burden of work-related musculoskeletal injuries in physiotherapists [3][4][5][6][7]. West and Gardner [7] reported that 16% of physiotherapists first experienced their injury as students, whereas 56% reported their worst injury to have occurred within the first 5 years of working as a physiotherapist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations